ENVIRONMENTAL SCARCITY AND GLOBAL SECURITY: THE ASSESSMENT OF ENVIRONMENT RELATED CONFLICTS IN BANGLADESH, SENEGAL-MAURITANIA, PHILIPPINES AND EL SALVADOR - Aydogan, Hakan (European Scientific Journal, ESJ, 2015)
Environmental threats and conflicts have become the epicenter of many problems we now face globally. The environmental problems do not concern just poor people in Third World countries, but also people in all over the World. This paper touches upon the significance of environment related problems in terms of global security. For this purpose it assesses some environmental conflict cases and discusses the importance of global cooperation to eliminate the environment related conflicts.